Association of genetic and climatic variability in giant sequoia, Sequoiadendron giganteum, reveals signatures of local adaptation along moisture‐related gradients. Issue 19 (1st September 2020) - DeSilva, Rainbow; Dodd, Richard S.
Abstract: Uncovering the genetic basis of local adaptation is a major goal of evolutionary biology and conservation science alike. In an era of climate change, an understanding of how environmental factors shape adaptive diversity is crucial to predicting species response and directing management. Here, we investigate patterns of genomic variation in giant sequoia, an iconic and ecologically important tree species, using 1, 364 bi‐allelic single nucleotide polymorphisms (SNPs). We use an F ST outlier test and two genotype–environment association methods, latent factor mixed models (LFMMs) and redundancy analysis (RDA), to detect complex signatures of local adaptation. Results indicate 79 genomic regions of potential adaptive importance, with limited overlap between the detection methods. Of the 58 loci detected by LFMM, 51 showed strong correlations to a precipitation‐driven composite variable and seven to a temperature‐related variable. RDA revealed 24 outlier loci with association to climate variables, all of which showed strongest relationship to summer precipitation. Nine candidate loci were indicated by two methods. After correcting for geographic distance, RDA models using climate predictors accounted for 49% of the explained variance and showed significant correlations between SNPs and climatic factors. Here, we present evidence of local adaptation in giant sequoia along gradients of precipitation and provide a first step toward identifying genomic regions of adaptive significance. The results of this study will provide information to guide management strategies that seek to maximize adaptive potential in the face of climate change. Abstract : We investigate patterns of genomic variation in giant sequoia, an iconic and ecologically important tree species, using 1, 364 bi‐allelic single nucleotide polymorphisms (SNPs). Using genotype–environment association and F ST outlier tests, we identify 79 genomic regions of potential adaptive importance, with limited overlap between the detection methods. The majority of the outlier loci show strong correlations to moisture‐related variables indicating local adaptation of giant sequoia populations along gradients of precipitation.